Dispatch automation system based low voltage distributed photovoltaic power station connected estimation model - Dayan MA; Xiangying XIE; Zhixiong NA; Wentao SHEN; Fanteng MENG (Dianxin kexue)
A large number of distributed photovoltaic access grids pose great challenges to the safe and stable operation of the grid.In view of the fact that the dispatching automation system did not realize the real-time acquisition and monitoring of low-voltage distributed photovoltaic data,the station estimation method was proposed as an auxiliary means for real-time acquisition of low-voltage distributed photovoltaic power plants,and the comprehensive low-voltage distributed photovoltaic power plants were estimateed through appropriate algorithms.Through case analysis,the deviation between the estimated value and the measured value was basically controlled within 8%,which proved the accuracy of the estimated model.This method is of great significance for the power dispatching department to strengthen the operation monitoring and statistical management of distributed photovoltaics,and to reasonably arrange the dispatching plan and coordinate the power supply.